Additional obstacles in carbon nanotube growth by gas-flow directed chemical vapour deposition unveiled through improving growth density. Issue 10 (17th September 2019) - Tsuji, Takashi; Hata, Kenji; Futaba, Don N.; Sakurai, Shunsuke
Abstract : We report growth of ultralong carbon nanotubes by combining a fast-heating chemical vapour deposition process with catalyst support engineering. Abstract : Here, we demonstrate an approach of increasing the density of ultralong carbon nanotube (CNT) growth by combining a fast-heating method developed by Huang et al. ( J. Am. Chem. Soc., 2003, 125, 5636–5637) with catalyst support engineering. Specifically, using graphene oxide as a catalyst support for iron oxide (Fe3 O4 ) catalyst nanoparticles, we achieved high density growth of CNTs grown by the "kite-mechanism". Our analysis revealed that the fast-heating method reduced undesired aggregation of the catalyst nanoparticles, which has been reported to be a primary limitation mechanism, by shortening the time between substrate heating and CNT growth. In addition, the use of the graphene oxide support led to controllable and uniform dispersion of catalyst nanoparticles in relatively high density which provided increased process control by extending the time before the onset of catalyst aggregation. Together, these approaches suppressed the aggregation of the catalyst nanoparticles, which facilitated the "tip-growth" mode instead of the "root-growth" mode, and led to the high density growth of ultralong CNTs. Our results also indicate additional limitations and complexities on the high density CNT growth by the kite-growth approach, which limit high density synthesis.